Foreign experience of creation and development of electronic government - Gulyamov, Saidakhror; Shermukhamedov, Abbas; Kholboev, Bokhodir (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The article analyzes the foreign experience in the creation and development of e-government